MANAJEMEN PEMBIAYAAN PENDIDIKAN TINGGI DALAM UPAYA PENINGKATAN MUTU (Studi Kasus Pada Perguruan Tinggi Swasta Menengah di Surabaya) - Anwar Abidin, Achmad (Jurnal Penjaminan Mutu, 2017)
Financing a good management is one key to the success of an educational institution to promote or increase quality. In this study, the focus of the problem is how the management of financing available to the private universities in Surabaya medium in order to improve its quality. The method used is qualitative descriptive with the presence of the researcher as an instrument of research conducted interviews to informants as a source of primary data and documents as well as supporting books as a secondary data source. Management Funding education is one of the factors that determine the quality improvement due to the financial management that is transparent and accountable will give rise to the belief of stakehoulder and it will be the motivation of each academicians Tri Dharma College in Private colleges medium in Surabaya to conduct quality improvement in their respective fields.